Involvement of reactive oxygen species during early stages of ectomycorrhiza establishment between Castanea sativa and Pisolithus tinctorius - Baptista, Paula (2008)
Evidence for the participation of reactive oxygen species (ROS) and antioxidant systems in ectomycorrhizal(ECM) establishment is lacking. In this paper, we evaluated ROS production and the activities of superoxide dismutase (SOD) and catalase (CAT) during the early contact of the ECM fungus Pisolithus tinctorius with the roots of Castanea sativa (chestnut tree). Roots were placed in contact with P. tinctorius mycelia, and ROS production was evaluated by determining the levels of H2O2 and O2 I− during the early stages of fungal contact. Three peaks of H2O2 production were detected, the first two coinciding with O2 I− bursts. The first H2O2 production peak coincided with an increase in SOD activity, whereas CAT activity seemed to be implicated in H2O2 scavenging. P. tinctorius growth was evaluated in the presence of P. tinctorius-elicited C. sativa crude extracts prepared during the early stages of fungal contact. Differential hyphal growth that matched the H2O2 production profile with a delay was detected. The result suggests that during theearly stages of ECM establishment, H2O2 results from an inhibition of ROS-scavenging enzymes and plays a role in signalling during symbiotic establishment.